Integrasi Ilmu dalam Perspektif Al-Qur'an - Muchlis Muhammad Hanafi (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Science integration can be found in the Qur'an by tracing the Qur'anic perspective in viewing object, source and the goal of sciences. The Qur'an contains the principles of values that enabled even obliged the effort for that integration. This is the explanation that the writer wants to show in this writing. There are some basic prin-ciples that oblige the muslim community to make their best effort in scientific methods concerning the way to uncover the secret of the universe and its application. Al-Qur'an does not recognize the dichot-omy of sciences–religious sciences and general sciences, worldly sciences and hereafter sciences. In Qur'anic view, science covers all the knowledge that is benefecial for all human kind for the their sustainable life at the present time or in the future.